On the Utilization of Dietary Glycerol in Carnivorous Fish - Part I: Insights Into Hepatic Carbohydrate Metabolism of Juvenile Rainbow Trout (Oncorhynchus mykiss) and European Seabass (Dicentrarchus labrax) - Viegas, Ivan; Tavares, Ludgero C.; Plagnes-Juan, Elisabeth; Silva, Emanuel; Rito, João; Marandel, Lucie; Palma, Mariana; Ozório, Rodrigo O. A.; Magnoni, Leonardo J.; Panserat, Stéphane (Frontiers in Marine Science, 2022)
The final version of the article will be published here soon pending final quality checks.